Decomposing the Effects of CCTs on Entrepreneurship - Lichand, Guilherme (2012)
Conditional cash transfers boosted a major reduction in poverty and a significant decrease in inequality in developing countries over the past decade. However, their success in promoting economic development is challenged by the claim that they deal with short-term poverty relief without providing the poor with the tools for breaking away from poverty by their own means. This claim, however, could be dismissed if conditional cash transfers had an effect on entrepreneurship. This paper assesses whether Bolsa-Familia increases the probability of starting a new venture in Brazil, decomposing its potential effects into three channels: alleviation of the wealth constraint, insurance against negative outcomes of risky activities, and reduction of the labor supply of children (through the effect of the conditionality). The effect of each of these channels is separately estimated using data from National Household Surveys in 2004 and 2006, for which the households of transfer beneficiaries can be identified. The results indicate that entrepreneurship is indeed stimulated by the program in urban areas throughout the insurance and wealth constraint alleviation effects, notwithstanding that new ventures are typically secondary sources of income. Finally, the conditionality seems not to have an impact on the level of entrepreneurship.